Experimental and Theoretical Study of an Intramolecular CF3‐Group Shift in the Reactions of α‐Bromoenones with 1, 2‐Diamines. Issue 47 (6th October 2015) - Muzalevskiy, Vasily M.; Ustynyuk, Yury A.; Gloriozov, Igor P.; Chertkov, Vyacheslav A.; Rulev, Alexander Yu.; Kondrashov, Evgeniy V.; Ushakov, Igor A.; Romanov, Alexey R.; Nenajdenko, Valentine G.
Abstract: The reactions of trifluoromethylated 2‐bromoenones and N, N ′‐dialkyl‐1, 2‐diamines have been studied. Depending on the structures of the starting compounds, the formation of 2‐trifluoroacetylpiperazine or 3‐trifluoromethylpiperazine‐2‐ones was observed. The mechanism of the reaction is discussed in terms of multistep processes involving sequential substitution of bromine in the starting α‐bromoenones and intramolecular cyclization of the captodative aminoenones as key intermediates to form the target heterocycles. The results of theoretical calculations are in perfect agreement with the experimental data. The unique role of the trifluoromethyl group in this reaction is demonstrated. Abstract : A subversive shift : The reactions of trifluoromethylated 2‐bromoenones with N, N ′‐dialkyl‐1, 2‐diamines afford 3‐CF3 ‐piperazine‐2‐ones by rearrangement with an unusual intramolecular CF3 ‐group shift (see scheme). In contrast, 2‐(trifluoromethyl)piperazine is obtained from the reaction with N, N ′‐dicyclopropylethylenediamine. The mechanism of the reaction is discussed and the unique roles of both the trifluoromethyl and cyclopropyl groups in this reaction are demonstrated.